Unusual Antarctic Mesospheric Cooling During 2019 SH Minor SSW - S.Eswaraiah; Kyong-Hwan Seo1; Kondapalli Niranjan Kumar; Jun Young Hwang; Wonseok Lee; M.Venkat Ratnam; G.Venkata Chalapathi; Chalachew Kindie Mengist; Yang Ha Kim (Zenodo, 2022)
Simultaneous meteor radar, MLS, and MERRA observations show that the Antarctic mesopause cooled to 26 K, in response to a 66 K warming in the stratosphere during the 2019 minor sudden stratospheric warming (SSW) in the Southern Hemisphere. Depressed gravity wave (GW) activity and the enhanced upward propagation of 10-day planetary waves (PWs) are prominent during SSWs. We observed an enhancement in carbon monoxide through carbon dioxide (CO 2 ) photolysis and a decrease in ozone (O 3 ) at 75 km during peak SSW. Hence, mesospheric cooling (MC) is due to the combined effects of PWs, CO 2 infrared cooling, and O 3 depletion but not the adiabatic cooling of GWs. PW analysis suggests that the chemical tracers that induced MC were uplifted from the lower atmosphere by anthropogenic and other sources and propagated through meridional circulation. Thus, the polar mesosphere was significantly affected by the 2019 SH SSW. Simultaneous meteor radar, MLS, and MERRA observations show that the Antarctic mesopause cooled to 26 K, in response to a 66 K warming in the stratosphere during the 2019 minor sudden stratospheric warming (SSW) in the Southern Hemisphere. Depressed gravity wave (GW) activity and the enhanced upward propagation of 10-day planetary waves (PWs) are prominent during SSWs. We observed an enhancement in carbon monoxide through carbon dioxide (CO 2 ) photolysis and a decrease in ozone (O 3 ) at 75 km during peak SSW. Hence, mesospheric cooling (MC) is due to the combined effects of PWs, CO 2 infrared cooling, and O 3 depletion but not the adiabatic cooling of GWs. PW analysis suggests that the chemical tracers that induced MC were uplifted from the lower atmosphere by anthropogenic and other sources and propagated through meridional circulation. Thus, the polar mesosphere was significantly affected by the 2019 SH SSW.